Normalized water supply through innovative public private partnership. (Asian Development Bank, 2017)
Public private partnerships (PPPs) are seen, in particular by the Government of India, as a mechanism to improve the performance of utilities and generate efficiency gains in the delivery of water services, even though their potential for leveraging private financing is much lower than was originally expected. ADB, together with other multilateral and bilateral financial institutions, has supported the design and implementation of alternative contract modalities that allow participation of the private sector to generate efficiency in design, construction, or operations of facilities, or a combination thereof, while relying on public funding. The performance-based construct and operate contract (PBCOC) that was initially used in Ilkal can be seen as a pragmatic introduction to PPPs, with the aim of ensuring sustainability of investments and effectively improving the delivery of water services for beneficiary populations.